2016
DOI: 10.1111/acer.13103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alcohol on Encoding and Consolidation of Memory for Alcohol-Related Images

Abstract: Background Drug and alcohol abusers develop strong memories for drug-related stimuli. Preclinical studies suggest that such memories are a result of drug actions on reward pathways, which facilitate learning about drug-related stimuli. However, few controlled studies have investigated how drugs affect memory for drug-related stimuli in humans. Methods The current study examined the direct effect of alcohol on memory for images of alcohol-related or neutral beverages. Participants received alcohol (0.8 g/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 47 publications
1
28
0
1
Order By: Relevance
“…Stimuli consisted of 144 images from the International Affective Picture Set (IAPS; Lang, Bradley, & Cuthbert, 2008) and 2–3 word labels (e.g., ‘angry man face,’ ‘sailboat on ocean’) describing these images, as well as 96 alcohol-related and non-alcoholic beverage-related images, data for which will not be reported here (see Weafer, Gallo, & de Wit, 2016b). The images included emotionally negative, neutral, and positive pictures and had the following mean normed valences and arousals, respectively: negative 2.95 and 5.66, neutral 5.31 and 3.71, positive 7.17 and 5.58.…”
Section: Methodsmentioning
confidence: 99%
“…Stimuli consisted of 144 images from the International Affective Picture Set (IAPS; Lang, Bradley, & Cuthbert, 2008) and 2–3 word labels (e.g., ‘angry man face,’ ‘sailboat on ocean’) describing these images, as well as 96 alcohol-related and non-alcoholic beverage-related images, data for which will not be reported here (see Weafer, Gallo, & de Wit, 2016b). The images included emotionally negative, neutral, and positive pictures and had the following mean normed valences and arousals, respectively: negative 2.95 and 5.66, neutral 5.31 and 3.71, positive 7.17 and 5.58.…”
Section: Methodsmentioning
confidence: 99%
“…They were also instructed to refrain from alcohol and other recreational drugs for at least 24 hours prior to each study session. Women using hormonal contraceptives were tested at any time in their menstrual cycle, but those not using contraceptives (n=3) were tested only in the follicular phase to control for fluctuations in endogenous hormone levels (Miller et al, 2016; Weafer, Gallo, & de Wit, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…That is intoxication reduces the formation of new memories thereby protecting already existing memories and making them less vulnerable to interference. Alcohol-induced retrograde facilitation has been demonstrated in previous studies using list of words, sentences, pictures and prose passages (Bruce and Pihl 1997 ; Moulton et al 2005 ; Parker et al 1980 ; Weafer et al 2016a , b ). Our findings demonstrate that alcohol-induced facilitation holds true for autobiographical memories in a misinformation eyewitness paradigm.…”
Section: Discussionmentioning
confidence: 68%
“…Similarly, Moulton et al ( 2005 ) found that although memory for prose learned while participants were intoxicated (mean peak BAC = .08%) was poor compared to sober controls, the opposite was found for prose learned prior to intoxication. The diphasic effect of alcohol on memory performance has been found with emotional (Bruce and Pihl 1997 ; M BAC = .06%), neutral, and alcohol-related stimuli (Weafer et al 2016a , b ; peak BAC = .08%). Thus, alcohol seems to impair subsequent recall of information encoded when intoxicated but facilitates recall of material encountered prior to intoxication due to minimizing general new memory formation (Wixted 2005 ).…”
mentioning
confidence: 96%